Behavior of Concrete Reinforcement Columns Subjected to Periodic Fire (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
One of the worst things that can happen to a structure is fire. Nonetheless, reinforced concrete remains one of the most extensively utilized building materials globally due to its high resistance. The skeletal components of reinforced concrete shift when exposed to high temperatures, which frequently results in inclusive cracking. The most crucial structural components in any concrete building are slabs, beams, and columns. In general, structural members are made to meet serviceability and safety limit state standards for a range of environmental circumstances. Structural members are usually designed to satisfy a particular fire resistance rating. Fire resistance depends on a number of factors, including the structure's attributes and the type of occupation. The main objectives of structural fire rating are to allow building occupants to evacuate, to provide firemen enough time to extinguish the fire, and to avoid any possible structural damage. The behavior of several reinforced concrete building structural components under high temperature exposure is summarized in this article. It has been discovered that fire negatively impacts both concrete and reinforcing bars. Additionally, it has been found that when stress or the length of time exposed to fire increases, stiffness and flexibility decrease. Additionally, as the cross-section of the structural element increases, the stiffness and flexibility increase as well; yet, during the fire test, the maximum slab deflection reduces nonlinearly. As temperatures drop, the concrete slabs bottom cools, increasing the bottom reinforcing's yield strength and causing it to shrink with the slabs lower half. As a historical review, this article also provides an analysis of a number of experimental and theoretical findings about the way that beams, slabs, and other structural elements made of reinforced concrete behave thermally under different conditions.